Rotatividade dos trabalhadores de enfermagem nos hospitais do município de Uberaba, Minas Gerais - Hemiko Iwamoto, Helena; Anselmi, Maria Luiza (Revista Gaúcha de Enfermagem, 2008)
This article measures and describes nursing staff turnover in eleven hospitals located in the city of Uberaba, Minas Gerais, Brazil, in 2003. The entire hospital network hired 327 nursing professionals and dismissed 276. Therefore, employment rate was higher than dismissal rate, with the exception of nursing assistants. Net replacement rate was of 24.3%. Entire nursing staff would be completely replaced in approximately 3,6 years. The indexes used indicated higher stability and lower staff turnover rate in public hospitals as compared to private hospitals.